A gestão da formação do professor para o trabalho com as tecnologias digitais móveis - Lopes, Henrique Bovo (2014)
This research investigated the management for the use of mobile digital technologies by teachers on a private school in the Greater ABC Region, a part of Metropolitan São Paulo, specifically the use of tablets, as a learning instrument in the classroom. The fact that new medias, in the current educational scenario, are part of the cultural universe in every student´s life and the fact that those same medias are being used out of the educational context or not being used with their real potential as a learning instrument (ALMEIDA, 2011) made this research sought to understand, under the optic of applied linguistic, the process of appropriation of mobile technologies by a group of teachers during a continuing teacher´s development program offered by the school.The research and the continuing teacher´s development under consideration are theoretically based on social cultural historical Activity Theory (VYGOTSKY, 1934; LEONTIEV, 1977; ENGESTRÖM, 1987-2009), on education and technologies concepts (ALMEIDA, 2008) and in the relationship between argumentation studies (LIBERALI, 2007, 2009, 2011; LIBERALI, FUGA, 2012; LIBERALI, MAGALHÃES, 2009; LIBERALI, MATEUS, DAMIANOVIC, 2012).It is also organized according to the methodological principles of Critical Collaborative Research (MAGALHÃES, 2009-2011), in which the coordinator/researcher and the teachers not only observe the educational context, but are also essential elements of the research process itself by promoting discussions and critical-collaborative dialogues, learning and collectively developing their professional skills. The data analysis object were the speeches, discussions and teachers´ productions during the continuing professional development. This project discuss the course of activities produced in a creative process and the argumentative language used during the management process of teacher´s development training regarding the use of mobile technologies as a learning instrument. The data showed that questions and answers provided by the participants were interwoven into a plan of discursive and argumentative action which have contributed to personal and professional growth of teachers and of the coordinator-researcher